STANDARD OPERATING PROCEDURE (SOP) FOR THE IMPLEMENTATION OF THE COLLECTION UNIT FUNCTION AT PT. KERETA API INDONESIA (PERSERO) DAOP 7 MADIUN: Standar Operasional Prosedur (SOP) Pelaksanaan Fungsi Unit Penagihan di PT. Kereta Api Indonesia (PERSERO) DAOP 7 Madiun - Dea Pravita Gunawan; Endang Murti; Bambang Martin Baru (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Standard Operating Procedures (SOPs) play a crucial role in contributing to the smooth operation of a company’s, operations, particularly in the accounts receivable collection process, which is directly related to financial management. At PT Kereta Api Indonesia (PERSERO), SOPs serve as work guidelines to ensure that asset lease collection activities are conducted in a orderly focused manner, and in accordance with established procedures. This study aims to analyze the implementation of Standard Operating Procedures in the Collection Unit at PT. Kereta Api Indonesia (PERSERO) and identify obstacles encountered during their implementation. This research used a descriptive qualitative approach, collecting data through observation, interviews, and documentation. Previous research on standard operating procedures focused on internal control of accounts receivable for asset lease operations, indicating that internal control of accounts receivable for asset lease operations at PT. Kereta Api Indonesia (PERSERO) Operational Area 7 Madiun was adequate. The findings of this study indicate that the implementation of the collection SOP has not been optimal. This is caused by differences with the actual conditions in the field which are not yet optimal because there are still tenants who have difficulty paying bills or are late in making payments, the high backlog or arrears not all debtors are handled quickly, as well as a lack of awareness and compliance for debtors.